2015
DOI: 10.1136/tobaccocontrol-2014-052018
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco product prices before and after a statewide tobacco tax increase

Abstract: Background In 2013, the State of Minnesota Legislature passed a tobacco tax increase that increased the combined cigarette excise and sales tax by $1.75 (from $1.60 to $3.35) and increased the tax on non-cigarette tobacco products from 70% to 95% of the wholesale price. The current study explores the change in tobacco prices in retail locations and whether the tax increase was fully passed to consumers. Methods An observational study of tobacco retail prices was performed in a sample of 61 convenience stores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 17 publications
1
28
0
3
Order By: Relevance
“…There is evidence from the UK,32 USA33 and New Zealand34 indicating that tobacco prices increase differently across product categories after taxation. Ongoing research is required to simulate the complexities of tobacco industry pricing strategies, and encourage more sophisticated responses from governments that mitigate against ‘down-trading’ to cheaper tobacco products.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence from the UK,32 USA33 and New Zealand34 indicating that tobacco prices increase differently across product categories after taxation. Ongoing research is required to simulate the complexities of tobacco industry pricing strategies, and encourage more sophisticated responses from governments that mitigate against ‘down-trading’ to cheaper tobacco products.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, only a few U.S. studies have provided a detailed characterization of cigarette price heterogeneity within states and counties by examining store-level prices. Three U.S. studies analyzed store-level price data [4,5,6] but they all focused on short time periods (≤2 year) and two focused on only a single geographic region [4,6]. …”
Section: Introductionmentioning
confidence: 99%
“…In the U.S., tobacco tax policy has used indirect taxes levied on the tobacco producer or vendor (“excise taxes”). Results of prior studies have been mixed regarding whether tobacco excise taxes are in fact fully passed on to the consumer [7,8], only partially passed on [5], or over-shifted [4,6,9,10,11]. Several studies have identified geographic differences in the pass-through rate [4,5] and two studies found differences by socioeconomic status [5,6], factors which may contribute to local variation in cigarette prices.…”
Section: Introductionmentioning
confidence: 99%
“…5,8,9,1113 However, several prior studies found substantial variation in cigarette prices within states and counties. 1416 In addition, prior work suggests geographically proximal exposures may be important determinants of smoking behavior- for example, individuals who lived closer to stores licensed to sell tobacco were less likely to quit smoking than those living farther away. 17,18 Thus, the tobacco retail environment near peoples’ homes may have a meaningful impact on their smoking behavior, and local cigarette prices may better reflect the prices to which they are exposed than state-level averages.…”
Section: Introductionmentioning
confidence: 99%